O conjunto solução da equação 3(x+1)-2(x-1) = -(x+5) é:
IsabelaBiasi:
3(x+1)-2(x-1)=-(x+5)
Respostas
respondido por:
2
resolução:
3x+3-2x+2= -x-5
x+x=-5-3-2
2x= -10
x= -10/2
x= -5
S= {-5}
3x+3-2x+2= -x-5
x+x=-5-3-2
2x= -10
x= -10/2
x= -5
S= {-5}
respondido por:
4
3(x+1)-2(x-1) = -(x+5)
3x + 3 -2x + 2 = -x-5
3x - 2x + x = -5 -3 -2
2x = -10
x = -10 / 2
x = -5
3x + 3 -2x + 2 = -x-5
3x - 2x + x = -5 -3 -2
2x = -10
x = -10 / 2
x = -5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás